Investigating Basic Writing Course: The Practices and Perceptions of Students at University Level - Mubasyira, Mu'thia (Universitas Indraprasta PGRI, 2025)
Basic writing as the first stepping stone course in learning English writing skills need to be taught properly. The current method used in university level in teaching basic writing is using Picture Word Inductive Model (PWIM). Nevertheless, this method is not implemented comprehensively. Therefore, this research is trying to collect primary data from students regarding their practices and perceptions for basic writing course with the current methods. The purpose of this study is to find out how the basic writing learning process by using PWIM and to analyze how students perceive in basic writing learning course and to describe the effectiveness of basic writing learning using PWIM. Respondents were 50 students of the English education study program at university level who took basic writing courses in the third semester. They are selected from four basic writing classes by using purposive sampling technique. This study used mixed methods where qualitative descriptive methods are used to find out and analyze the learning process and perception of students in basic writing classes based on the results of semi-structural interviews conducted and also based on the results of questionnaires distributed to the 50 students. While the experimental method with pretest-posttest design is carried out to find out the effectiveness of basic writing learning using PWIM. Before the data is processed, researchers conduct assumption tests such as tests of normality. After that, a paired t-test is performed. The result showed that the learning process with this approach still needs to be improved, especially about consistency in using this PWIM approach. Then related to the perception of students toward basic writing course also needs to be considered as feedback on better basic writing learning. Furthermore, the results of statistical calculations illustrate that this approach has an influence in the implementation of the effective basic writing classes.